If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8ln(11 + -6x) = 4 (11 * 8ln + -6x * 8ln) = 4 (88ln + -48lnx) = 4 Solving 88ln + -48lnx = 4 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -4 + 88ln + -48lnx = 4 + -4 Combine like terms: 4 + -4 = 0 -4 + 88ln + -48lnx = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-1 + 22ln + -12lnx) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-1 + 22ln + -12lnx)' equal to zero and attempt to solve: Simplifying -1 + 22ln + -12lnx = 0 Solving -1 + 22ln + -12lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 22ln + 1 + -12lnx = 0 + 1 Reorder the terms: -1 + 1 + 22ln + -12lnx = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 22ln + -12lnx = 0 + 1 22ln + -12lnx = 0 + 1 Combine like terms: 0 + 1 = 1 22ln + -12lnx = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 5x-9-x=7 | | x+5=9x-3 | | xa^2=c-b | | 5x-4+2x=2x+1 | | 6m+16=45x+18-13 | | 1.5h-5=1 | | 4x+31=12x-39 | | ax^2=c-b | | n-n-12=0 | | 11.8-3.4v=6(4.1-v) | | 64+4x=180 | | x+2=3x+1 | | 3(3x-4)=4(2x+1) | | (n+2)*4=5 | | 238-3w=190 | | -3(r-1/3)=3 | | 32=n-4 | | -9=3(p-1) | | 35x^2-37x-6=0 | | -4-3x=9x+20 | | 2b-b=5-2b | | -94=-1-3(1-6a) | | 11+9x=59+37x | | 2b=b-2b | | v-11=28 | | -4-3=9x+20 | | x+64=12 | | -5x-5x= | | 15-3(x+3)=21 | | 7x+17=4x-25 | | 2n-9+3=4n+1 | | 5[1.5(x-1)-6.8]-0.31x=3.7 |